2008
DOI: 10.1095/biolreprod.107.067413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antiestrogen Fulvestrant (ICI 182,780) on Gene Expression of the Rat Efferent Ductules1

Abstract: The efferent ductules express the highest amount of estrogen receptors ESR1 (ERalpha) and ESR2 (ERbeta) within the male reproductive tract. Treatment of rats with the antiestrogen fulvestrant (ICI 182,780) causes inhibition of fluid reabsorption in the efferent ductules, leading to seminiferous tubule atrophy and infertility. To provide a more comprehensive knowledge about the molecular targets for estrogen in the rat efferent ductules, we investigated the effects of ICI 182,780 treatment on gene expression us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 74 publications
6
44
0
Order By: Relevance
“…Rats were treated once a week for 2 months with corn oil (control group) or ICI 182,780 (10 mg/ rat, s.c., AstraZeneca), starting at an age of 30 days. This treatment does not alter plasma estradiol and testosterone (Yasuhara et al 2008).…”
Section: In Vivo Treatmentsmentioning
confidence: 82%
See 2 more Smart Citations
“…Rats were treated once a week for 2 months with corn oil (control group) or ICI 182,780 (10 mg/ rat, s.c., AstraZeneca), starting at an age of 30 days. This treatment does not alter plasma estradiol and testosterone (Yasuhara et al 2008).…”
Section: In Vivo Treatmentsmentioning
confidence: 82%
“…Anti-estrogen treatment Animals were treated as previously described (Oliveira et al 2002, Yasuhara et al 2008. Rats were treated once a week for 2 months with corn oil (control group) or ICI 182,780 (10 mg/ rat, s.c., AstraZeneca), starting at an age of 30 days.…”
Section: In Vivo Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a microarray analysis of genes differentially expressed in the efferent ductules of fulvestrant-treated animals, we have been able to identify a significant impact of the antiestrogen treatment on gene expression, and besides genes related to ion and water transport, genes related to extracellular matrix organization and sperm maturation and/or capacitation, among others, were also affected, suggesting a broader role of estrogen to regulate the morphology and function of the efferent ductules (52).…”
Section: Efferent Ductulesmentioning
confidence: 99%
“…In addition, a recently reported study suggested that LECT-1 may participate in the innate immune defense system of the disk abalone (Haliotis discus discus) [14]. Furthermore, it should be noted that a down-regulation of the LECT-1 gene expression has been observed in the rat male reproductive tract following treatment with the estrogen receptor antagonist Fulvestrant [15].…”
Section: Seldi-tof Ms Elutionmentioning
confidence: 97%